Clinical Case of Mccune-Albright-Braitsev Syndrome (MAS) - F. V. Valeeva; T. A. Kiseleva; M. R. Shaidullina; D. R. Islamova; A. K. Gumerova (Медицинский вестник Юга России, 2023)
The presented clinical case describes orphan disease known as MAS with manifested symptoms of precocious puberty, recurrent ovarian cysts, fibrous dysplasia, café-au-lait skin pigmentation and abnormal cardiac conduction. The pathogenesis is based on the GNAS gene mutation that cause hyperactivation of glycoprotein hormone receptors and hypersecretion. There are genetic tests that confirm the diagnosis, however, given the high percentage of false negative results, in most cases the disease is diagnosed based on a combination of clinical and laboratory-instrumental data. Given the high clinical variability and absence of management algorithms for patient with this syndrome, the article pinpoints the necessity of thorough examination of patients to select further management tactics. Multidisciplinary approach and collegiate case management will improve diagnosis of the disease and prevent the development of severe complications.